An approach to study electron and positron scattering from NH3 and PH3 using the analytic static potential. (22nd October 2020) - Mahato, Dibyendu; Sharma, Lalita; Srivastava, Rajesh
Abstract: A detailed study of the elastic scattering of electrons and positrons from two C3v symmetrical molecules viz ammonia and phosphine molecules is presented. The partial wave phase shift analysis method with complex optical potential consisting of static, exchange, polarization and an imaginary absorption potentials has been used. In contrast to the previously used similar approaches, the present method is quite different in the sense that we have obtained the required static potential in an analytical form using correctly represented Gaussian molecular wave functions for NH3 and PH3 in our calculations. The differential, integrated, momentum transfer, absorption and total cross sections are calculated and reported in the incident electron and positron energy range of 10–500 eV. In order to test the applicability of our approach, the present results are compared with the available previous measurements and theoretical calculations and a good agreement is found.